Utilizing System Dynamics for Border Area Development in Napan Village, North Bikomi, East Nusa Tenggara - Suryono Hadi, Yoos; Khusaisni, Moh.; Fadli, Moh.; Kusumaningrum, Adi (Journal of Social and Policy Issues, 2024)
Napan Village, North Bikomi District - North Central Timor Regency - East Nusa Tenggara is some of the areas that border Indonesia on land with neighboring countries. Napan Village shares a land border with Timor Leste. Various issues regarding security, prosperity and the environment in development often arise. This research was conducted to develop models dynamically in three development scenarios using these three approaches. The research sample was obtained using a questionnaire distributed to 78 respondents consisting of village soldiers and police, Napan village officials, the North Bikomi sub-district head, and border officers in Napan village. From the results of the questionnaire, descriptive analysis and multiple regression analysis were carried out to obtain a regression model of the influence of security, prosperity, and environmental approach variables on border area development. Next, the analysis results are used to develop a system dynamics model with three simulation scenarios. The reference used in this simulation is the average data value for each variable minus and adding one standard deviation and the equation resulting from multiple regression analysis. The simulation results show that the target for achieving development in border areas will reach 73% within 5 years if input from security, prosperity, and environmental factors is increased from the current condition of 8% for security, 6% for prosperity, and 9% for the environment. Furthermore, it is recommended to increase development on factors in security, prosperity, and environmental approaches according to these results so that in the next five years significant progress can be achieved, which reaches almost double the current conditions.